Demonstration of impaired T cell regulation of Epstein-Barr virus stimulated B lymphocytes in rheumatoid arthritis with HLA identical, disease discordant sibling pairs. - Fawcett, M C (1988)
Lymphocytes from patients with rheumatoid arthritis (RA) show an abnormal response after stimulation with Epstein-Barr virus (EBV), a potent B cell mitogen. In vitro IgM production from EBV stimulated lymphocytes was measured over a 21 day period. In keeping with previous studies, RA lymphocytes showed increasing IgM production between 14 and 21 days, whereas IgM production decreased during this period in normal lymphocytes (p less than 0.001). Experiments on 12 HLA identical, RA discordant sibling pairs were also undertaken. B enriched and T enriched lymphocyte populations were obtained and recombined in both an autologous and homologous manner. The abnormality in IgM production in patients with RA was shown to reside in the RA T cell population (p less than 0.005), and RA B cells combined with normal T cells behaved similarly to autologous cultures of normal B and T cells. The study shows that impaired immunoregulation of EBV stimulated B cells in RA is secondary to a functional defect in RA T cells, but no difference in the concentration of T suppressor/cytotoxic cells could be found between the disease discordant siblings. The abnormality in immunoregulation appears to be secondary to RA, rather than a product of genes encoded within the major histocompatibility complex (MHC) region, as defined by HLA-DR, A, B, and C typing.